Patient-controlled encrypted genomic data: an approach to advance clinical genomics - Trakadis Yannis J (BMC, 2012)
Abstract Background The revolution in DNA sequencing technologies over the past decade has made it feasible to sequence an individual's whole genome at a relatively low cost. The potential value of the information generated by genomic technologies for medicine and society is enormous. However, in order for exome sequencing, and eventually whole genome sequencing, to be implemented clinically, a number of major challenges need to be overcome. For instance, obtaining meaningful informed-consent, managing incidental findings and the great volume of data generated (including multiple findings with uncertain clinical significance), re-interpreting the genomic data and providing additional counselling to patients as genetic knowledge evolves are issues that need to be addressed. It appears that medical genetics is shifting from the present "phenotype-first" medical model to a "data-first" model which leads to multiple complexities. Discussion This manuscript discusses the different challenges associated with integrating genomic technologies into clinical practice and describes a "phenotype-first" approach, namely, "Individualized Mutation-weighed Phenotype Search", and its benefits. The proposed approach allows for a more efficient prioritization of the genes to be tested in a clinical lab based on both the patient's phenotype and his/her entire genomic data. It simplifies "informed-consent" for clinical use of genomic technologies and helps to protect the patient's autonomy and privacy. Overall, this approach could potentially render widespread use of genomic technologies, in the immediate future, practical, ethical and clinically useful. Summary The "Individualized Mutation-weighed Phenotype Search" approach allows for an incremental integration of genomic technologies into clinical practice. It ensures that we do not over-medicalize genomic data but, rather, continue our current medical model which is based on serving the patient's concerns. Service should not be solely driven by technology but rather by the medical needs and the extent to which a technology can be safely and effectively utilized.